2005
DOI: 10.1209/epl/i2005-10201-5
|View full text |Cite
|
Sign up to set email alerts
|

Casimir force between two ideal-conductor walls revisited

Abstract: PACS. 05.20.Jj -Statistical mechanics of classical fluids. PACS. 12.20.-m -Quantum electrodynamics. PACS. 11.10.Wx -Finite-temperature field theory.Abstract. -The high-temperature aspects of the Casimir force between two neutral conducting walls are studied. The mathematical model of "inert" ideal-conductor walls, considered in the original formulations of the Casimir effect, is based on the universal properties of the electromagnetic radiation in the vacuum between the conductors, with zero boundary condition… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
63
0

Year Published

2006
2006
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(74 citation statements)
references
References 27 publications
11
63
0
Order By: Relevance
“…And there are other papers in agreement with ours: for instance, Jancovici andŠamaj [14], and Buenzli and Martin [15] considered the Casimir force between two plates in the high-temperature limit. They found that the linear dependence in T for the Casimir force to be reduced by a factor of two from the behavior of of an ideal metal, this being a signal of the vanishing influence from the zero-frequency TE mode.…”
Section: Introductionsupporting
confidence: 87%
“…And there are other papers in agreement with ours: for instance, Jancovici andŠamaj [14], and Buenzli and Martin [15] considered the Casimir force between two plates in the high-temperature limit. They found that the linear dependence in T for the Casimir force to be reduced by a factor of two from the behavior of of an ideal metal, this being a signal of the vanishing influence from the zero-frequency TE mode.…”
Section: Introductionsupporting
confidence: 87%
“…In particular, the lack of a thermodynamic inconsistency has been conclusively demonstrated [33,34], by showing that the free energy for a Casimir system made from real metal plates with impurities has a quadratic temperature dependence at low temperature. Further evidence for the validity of the notion of excluding the TE zero mode for metals comes from the recent work of Buenzli and Martin [35], corroborating earlier work by these authors and others [36,37], who show from a microscopic viewpoint that the high-temperature behavior of the Casimir force is half that of an ideal metal, a rather conclusive demonstration that the TE zero mode is not present. 1 Our purpose with the present paper is not to study the temperature corrections in further detail.…”
Section: Introductionsupporting
confidence: 70%
“…At large separations or high temperatures the Drude model approach predicts 1/2 the magnitude of the Casimir free energy and force than between ideal metals. (The same prediction was obtained using the model of a conducting wall by the classical Coulomb fluid [16] or 'nonrelativistic quantum electrodynamics' [17].) This prediction is in contradiction with the classical limit based on Kirchhoff's law [18].…”
Section: Two Main Approaches To the Presentation Of Reflection Coeffisupporting
confidence: 54%